Nitrogen Response Behaviour of Developed Promising Lines of T.Aman Rice - Saha, PK; Islam, SMM; Akter, M; Zaman, SK (Bangladesh Journal of Agricultural Research, 2012)
Nitrogen is the most limiting nutrient for rice. Modern high yielding rice varieties may have differences in accumulating and using N from soil and applied fertilizer. A field experiment with 8 rice genotypes was conducted during 2008 wet season (T.Aman season) to study the effect of different rates of N fertilization on the yield performance and nitrogen nutrition under irrigated condition. Among the tested varieties/lines, BR7155-20-1-3 produced the significantly highest grain yield of 5.04 t/ha at N30 level followed by Swarna (4.66 t/ha) at the same level of N with similar growth duration (140 days). Agronomic efficiency of added N ranged from 0.7 to 23.3 for the promising line BR7155-20-1-3 and 3.3 to 27.0 for variety Swarna. Grain yield at No was the highest in BR7155-20-1-3 followed by the variety Swarna and the lowest in BR7870-5 *(Nils)- I 0-HR8. Percent nitrogen recovery ranged from 50 to 63 for variety Swarna and 13 to 30 for promising line BR7155-20-1-3. The promising line BR7155 20-1-3 and the variety Swarna may be economically advantageous over the other varieties/ lines. DOI: http://dx.doi.org/10.3329/bjar.v37i2.11222 Bangladesh J. Agril. Res. 37(2): 207-213, June 2012